The effect of various systems of tillage on microbiological processes in the rhizosphere of soybean - T. V. Gorgulko; S. V. Didovich (Зерновое хозяйство России, 2018)
The effect of various systems of tillage on microbiological processes in the rhizosphere of soybean The article gives the three-year study results of the formation and functioning of microbic associations in the rhizosphere of soybean under effect of various systems of tillage, i.e. plowing on the depth of 22-24 cm, surface plowing (6-8 cm), disk tillage and non-till technology. It has been shown that the period of plant development and the system of tillage influenced on the formation of soil macrobiocenosis in the rhizosphere. It has been determined that the number of aminotrophic microorganisms in the period of plant tilling combined with surface plowing and plowing was 39.1-56.3х105 of colony formatting units per gram of absolutely dry soil (CFU/g of a.d.s.) that was in 1.1-1.2 times higher compared with dist plowing and No-till. During the period of flowering there was an increase of nitrogen fixating microorganisms in all variants of tillage. Large number of cellulose-destroying microorganisms was seen in all periods of plant development that testified cellulose-destroying activity. On average in the years of 2012-2014 the level of catalase activity increased to 14.5 ± 1.8 ml O2/min under the influence of plowing to a depth of 22-24 cm in the period of plant maturation, which is on 36.6% higher compared with the period of plant flowering. The soybean productivity under the influence of plowing, disking and surface plowing was 3.27; 3.27 and 3.22 t/ha, which is on 12.1-13.5% more in comparison with No-till technology.